Paracetamol versus meperidine for relief of labour pain in primiparous women: a randomized controlled trial - Habib, Sherif M.; Mostafa, Mohamed H.; Salama, Mohamed H.; Swilam, Hend G. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Most parturient women request analgesia, of which, there are two types; opioids and non-opioids. Opioids include morphine and meperidine, while non-opioids, which are milder forms of painkillers, include acetaminophen (paracetamol) and non-steroid anti-inflammatory drugs. The major concerns associated with opioids are the risk of neonatal respiratory depression, the cost and availability. Methods: The aim of this study was to compare the efficacy and safety of paracetamol versus meperidine for intra-partum pain relief. A total of 92 primiparous singleton term pregnant women were randomly allocated to receive intravenous paracetamol (1000 mg), or intramuscular meperidine (50 mg), at the beginning of the active phase of labor. The primary outcome was the labor pain perception, assessed using the visual analogue scale (VAS), at baseline, 15, 30, 60 and 120 minutes after administration of the drug. Results: Women of both groups showed significant reduction of the VAS after administration of the medication. There were no differences between both groups regarding the mode of delivery and the durations of the first or second stages of labor. However, meperidine was associated with higher rates of dizziness and nausea/vomiting. The 1-min Apgar scores were significantly lower in meperidine group. However, there were no differences in the 5-min Apgar score, need for neonatal resuscitation or neonatal respiratory distress. Conclusions: intravenous paracetamol as analgesia during labor is effective with no fetal or maternal adverse effects. Its use should have more chance for intrapartum pain relief. Additionally, it can be used as adjuvant with other types of analgesics.